Razvoj cepiv proti virusu SARS-CoV-2 - Bratkovič, Tomaž (Farmacevtski vestnik, 2020)
The enormous impact of covid-19 pandemic on everyday life, global economy and healthcare has stimulated the fast-tracked development of SARS-CoV2 vaccines. Development is directed also towards promising innovative although not yet established platforms, such as vector vaccines and DNA and RNA-based vaccines. The SARS-CoV-2 vaccine development is projected to cost about 2 billion USD and take 12 to 18 months. 115 vaccines are currently being developed, of which 73 are in the preclinical phase and 10 in the first or second stage of a clinical trials. Only the results of the third stage of trials, which will include thousands of volunteers and their longterm monitoring, will give an answer as to whether the vaccine achieves the desired protection against the pathogen. On the way to the ultimate goal of a safe, effective and accessible vaccine, significant barriers to cost-effective production will still need to be overcome, especially for new platforms for which production infrastructure does not yet exist.
Keywords: Cepiva; pandemija covid-19; Pandemije; SARS-CoV-2